Distribution prediction of the habitat of Jingmen tick virus in China - Weiyi Li; Rongting Li; Chengyao Liu; Jinzhi Cheng; Lin Zhan; Zhengling Shang; Jiahong Wu (Microbiology Spectrum)
ABSTRACT Jingmen tick virus (JMTV) is widely distributed in China, and human cases have been reported. Therefore, the objectives of this study were to understand the distribution of the JMTV in suitable areas in China under the current and projected future climates. We used two pairs of JMTV primers to detect ticks in Guizhou Province via PCR and obtained data on JMTV detection in other regions through literature research. We obtained climate data from China. Finally, maximum entropy, a boosted regression tree model, and a random forest model were used for prediction. The predictive performance of the model was evaluated by the area under the curve (AUC) of the receiver operating characteristic (ROC) curve. The JMTV positivity rate in Guizhou Province was 11.02%, which was lower than the overall national positivity rate of 16.9%. The predicted probability increased monotonically with increasing monthly mean temperature. China’s high JMTV habitat is concentrated in the Daxinganling region of Heilongjiang, Shanghai, and Hainan Provinces, with the total area of high JMTV habitat accounting for 1.94% of the country’s total land area. In the future, from 2021 to 2040, the area of JMTV habitat area in China will show an expanding trend. Our maps of JMTV distributions provide effective early warning information for monitoring JMTV and rapidly detecting outbreaks. The potential distribution of JMTV in China is expected to increase in size in the future, requiring continuous attention and surveillance.IMPORTANCESince the first detection of the Jingmen tick virus (JMTV) in ticks in 2014, it has been detected on several continents around the world. JMTV has also been detected in several regions of China, and human cases have been reported. JMTV has many types of hosts, including ticks, mice, bats, and turtles. It can be spread with these hosts in close proximity or over long distances. As a segmented virus, JMTV is capable not only of genetic mutation and recombination but also of genetic reassortment, resulting in changes in viral infectivity or pathogenicity. However, many uninvestigated areas still exist in China. Therefore, we investigated ticks carrying JMTV in Guizhou Province. We also predicted the distribution of JMTV in China by combining previous data.